33 Incidence of intracranial haemorrhage associated with antiplatelet and anticoagulant use; referrals to the national neurosurgery referral centre and reports to the health products regulatory authority. (7th October 2015) - Cuddy, S; Sheahan, R; Collis, R; Matullah, S
Abstract : Intracranial Haemorrhage (ICH) is a feared side effect of antiplatelet and anticoagulant agents; it is of particular prominence with the advent of the novel antiplatelet and anticoagulant agents. Postmarket Reports of Bleeding with NOACs highlighted the fact that newly marketed products, by virtue of their novelty alone, may elicit adverse-event reports at high rates; reporting rates decreasing over time (the Weber effect). Hence established medications, such as Warfarin and Aspirin, would be far less likely to elicit adverse-event reports than would newer medications with similar risks. The hypothesis of this study was to examine the frequency of antiplatelet and anticoagulant associated ICH (AAICH) in a consecutive series of patients referred to a National Neurosurgical Centre. We also compared the number of referrals of AAICH to the National Neurosurgical Centre in Beaumont Hospital with the number of ICH reported to the Health Products Regulatory Authority (HPRA) as an adverse event of these medications. The National Neurosurgical Centre in Beaumont has an estimated referral population of 4 million. All consecutive referrals from July 2013 to January 2014 were reviewed. Data collected included baseline demographics, antiplatelet/anticoagulation usage and indication for same, and CT brain findings of the ICH. The HPRA were contacted and supplied their adverse event reports for the same period. There were 977 consecutive patients with an ICH referred in this period. Of these 328 (33.6%), with a mean age of 77 yrs, female 42.6%, were on an antiplatelet and/or an anticoagulant agent; ASA alone (n = 166, 50.6%), Warfarin alone (106, 32.3%), Clopidogrel alone (11, 3.3%), Rivaroxaban alone (4, 1.2%), Dabigatran alone (4, 1.2%), ASA/dipyridamole alone (3, 0.9%). Thirty one (9.4%) patients were on two agents, 19 on ASA and Clopidogrel, 7 on ASA and Warfarin, 2 on Clopidogrel and Warfarin, 2 on Rivaroxaban and ASA, and 1 patient on ASA and Prasugrel. Three patients were on 3 agents, 2 on ASA, Clopidogrel and Warfarin, one on ASA, Clopidogrel and Rivaroxaban. We excluded 22 patients who had an ICH following thrombolysis or recent heparin therapy. The HPRA received 4 reports of ICH associated with antiplatelets or anticoagulants; 2 associated with Warfarin, 1 with Rivaroxaban and 1 with Rivaroxaban and Warfarin. This study highlights ASA as the most frequently documented antiplatelet/anticoagulant agent in a real life consecutive series of patients referred to a Neurosurgical Unit with ICH. In discussing the role of anticoagulation with patients, particularly the elderly, the significant risk of bleeding with ASA needs to be considered. These results also highlight the lack of adverse reporting with new and old medications alike. It emphasises the importance of reporting to national authorities so their statistics can be a true reflection of the number of adverse events, especially when these outcomes can be catastrophic, like ICH.